Choroidal structural features of acquired vitelliform lesions in non-exudative age-related macular degeneration. Issue 1 (January 2023) - Demirel, Sibel; Yanık, Özge; Özcan, Gökçen; Batıoğlu, Figen; Özmert, Emin
Purpose: To define the choroidal morphological characteristics of non-exudative age-related macular degeneration (AMD) cases associated with acquired vitelliform lesions (AVLs). Methods: This retrospective study included intermediate AMD patients with AVLs (Group1, 21eyes) and without AVLs (Group2, 21eyes). A healthy control group was (Group3, 23eyes) also included. Subfoveal choroidal thickness (SFCT), greatest basal diameter (GBD), and maximum height (MH) of the largest PED were measured on spectral domain optical coherence tomography. Internal reflectivity of PEDs and total choroidal area (TCA) were measured using ImageJ software. The TCA was binarized to the luminal area (LA) and stromal area. The choroidal vascularity index (CVI) was assessed. Results: The mean SFCT, TCA, and LA were higher in Group 1 (290.3 ± 86.8 μm, 0.840 ± 0.302 mm 2, 0.602 ± 0.227 mm 2 ) than in Group 2 (215.6 ± 85.0 μm, 0.594 ± 0.183 mm 2, 0.429 ± 0.139 mm 2 ) ( p  = 0.014, p  = 0.017, p  = 0.020, respectively). There was no significant difference in the CVI measurements between Group 1 and Group 2 (p = 1.000). The mean GBD and MH of the PED was higher in Group 1 (1443 ± 595 µm, 188 ± 86 µm) than in Group 2 (851 ± 368 µm, 119 ± 38 µm) ( p  = <0.001, p  = 0.001, respectively). Internal PED reflectivity was significantly lower in Group 1 (0.44 ± 0.21) than in Group 2 (0.66 ± 0.17) ( p  = <0.001). Internal PED reflectivity showed negative correlation with GBD and MH of the PED in Group 1 (r = −0.587, p  = 0.005; rho = −0.448, p  = 0.042, respectively). In Group 2, internal PED reflectivity had a negative correlation with MH of the PED (rho = −0.511, p  = 0.018). Conclusion: Non-exudative AMD patients with AVLs are more prone to have a thick choroid and large hyporeflective PEDs as compared to the those without AVLs.